ANALISIS PERBANDINGAN PENGHIMPUNAN DAN PENYALURAN ZAKAT MASA PANDEMI COVID-19 (STUDI DI BADAN AMIL ZAKAT NASIONAL KOTA DAN KABUPATEN BOGOR) - Muhamad Rizal Gunawan; Ermi Suryani; Susi Melinasari (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
The National Amil Zakat Agency (BAZNAS) in Bogor is found in each Bogor City and Regency. However, people are still not familiar with BAZNAS, moreover they have a routine of setting aside their zakat at BAZNAS. Currently, the impact of the pandemic is still being felt and causing people's income to decline. Because the impact of the pandemic has disrupted activities, including collection and distribution activities to amil zakat institutions everywhere, this is a challenge in itself during this pandemic. These challenges range from updating and adjusting the collection and distribution procedures according to the impact of Covid-19, to BAZNAS in Bogor City or Regency constantly having innovations to improve collection and distribution. Under these circumstances, this research was conducted. The method used in this research is a quantitative method with a comparative approach. Based on the research conducted, in terms of collection comparisons, a Sig value of 0.094 > 0.05 was obtained. Thus Ho is rejected and Hi is accepted. This means that there are differences in the collection of BAZNAS City and Bogor Regency data. Based on the research that was also carried out, in terms of distribution comparison, a Sig value of 0.01> 0.05 was obtained. Thus Ho is accepted and Hi is rejected. This means that there is no difference in the distribution data of BAZNAS Kota and Bogor Regency.